2011
DOI: 10.1007/s00125-011-2164-y
|View full text |Cite
|
Sign up to set email alerts
|

Deep breathing improves blunted baroreflex sensitivity even after 30 years of type 1 diabetes

Abstract: Aims/hypotheses Cardiovascular autonomic neuropathy is associated with increased morbidity in patients with type 1 diabetes. Although it is conventionally considered to be an organic, irreversible disorder, we previously demonstrated in patients with short-duration type 1 diabetes that reduced baroreflex sensitivity (BRS) could be corrected by slow, deep breathing, indicating a functional component to the disorder. We have now tested whether autonomic abnormalities in long-term diabetes progress to a stage tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…The potential reversibility of BRS and low prevalence of definite CAN in our patients (3,4) is in line with observations that the prevalence of diabetes complications seems to decrease (5,6). The concept of functional autonomic dysfunction does not diminish the importance of an early diagnosis given that the prognostic value of reduced BRS has undoubtedly been proven in hypertension, renal failure, postmyocardial infarction, heart failure, and cerebral stroke (79)—conditions associated with functional alterations in the autonomic nervous system.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The potential reversibility of BRS and low prevalence of definite CAN in our patients (3,4) is in line with observations that the prevalence of diabetes complications seems to decrease (5,6). The concept of functional autonomic dysfunction does not diminish the importance of an early diagnosis given that the prognostic value of reduced BRS has undoubtedly been proven in hypertension, renal failure, postmyocardial infarction, heart failure, and cerebral stroke (79)—conditions associated with functional alterations in the autonomic nervous system.…”
supporting
confidence: 91%
“…The importance of early diagnosis lies in the fact that established CAN is associated with increased risk of diabetes complications (1) and mortality (2). However, in our recent studies in patients with type 1 diabetes with short (3) or long (4) duration, we demonstrated that reduced baroreflex sensitivity (BRS), an early marker of autonomic impairment, was markedly improved by slow, deep breathing. Notably, the patients had, regardless of duration of diabetes, blunted BRS that could be restored by deep breathing, except in those with definite CAN.…”
mentioning
confidence: 94%
“…elderly, hypertensive or diabetic patients). However, the enhancement of baroreflex sensitivity during 0.1 Hz breathing was also found in patients with diabetes [25] or chronic obstructive pulmonary disease [26]. In the setting of paced breathing, we used the same inspiration and expiration times to provide equal opportunity for the occurrence of up and down sequences.…”
Section: Limitationsmentioning
confidence: 94%
“…Regular exercise has been shown to improve HRV parameters in patients with CAN (Table 4) with a deterioration of those parameters within weeks of complete exercise withdrawal [109]. [90] also appears to be useful in improving BRS in DM patients regardless of the duration (except of course in those with marked CAN). Alpha-lipoic acid (ALA) shows promise in potentially improving BRS in diabetic patients due to the results already obtained in experimental models [86].…”
Section: Clinical Perspective On Interventional Modalitiesmentioning
confidence: 99%